Integration of eucs variables into delone and mclean models for e-government evaluation: Conceptual models - Sorongan, Erick; Hidayati, Qory (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2020)
This research was based on the modification of the DeLone and McLean information systems models by adding end-user computing satisfaction variables to determine the success factors for e-government systems. This model was adopted due to the aim of this study to investigate the factors responsible for the successful implementation of e-government by bringing it closer to public value. However, while the DeLone and McLean models focus more on the information system approach, the model proposed was on the premise that system quality (SQ), information quality (IQ), content (CO) and format (FO) are determinants of e-government system user satisfaction. Furthermore, the net benefits through a five-dimensional public value determinants were used to evaluate e-government websites from a community perspective. Responses from 150 communities were analyzed by smart PLS 3.0 using structural equation models to examine the relationship between the constructs of the proposed model. This study contributes to the research gap in adopting DeLone and McLean's model in the e-government due to the limitation in its validation for different contexts. The results support the effect of content variables on user satisfaction and simultaneously prove that it is possible to explain net benefits, with an r-squared value of 69.1%, using the variables in the proposed model. The five dimensions of public value adopted all proved to have a positive influence with a confidence level of 95%. The level of construct significance identified is able to help in the formulation of strategies to improve e-government services.